Carbohydrate Antigen-125 - Vijay U. Rao, MD, PhD; Thomas Fretz, MD; Tina Ayeni, MD; Kerry Skurka, BSN; Meghana Raghavendra, MD; Ankur Kalra, MD, MS (JACC: Case Reports, 2025)
Background: Carbohydrate antigen-125 (also known as cancer antigen-125) (CA-125) is a biomarker used to monitor for endometrial cancer progression, but it may also reflect other disease processes. Case Summary: A 70-year-old woman with metastatic endometrial cancer who was treated with paclitaxel, carboplatin, and pembrolizumab presented with new onset ascites and rising CA-125 levels concerning for cancer progression. She received a diagnosis of heart failure (HF) and normalized her CA-125 levels with loop diuretic agents without changing her oncologic treatment. Discussion: CA-125 is a novel biomarker for HF monitoring because it correlates with increased intracardiac filling pressures. In this patient, concomitant endometrial malignant disease and HF complicated ascertainment of ascites and elevated biomarker origin. Therefore, clinicians should consider alternate causes of elevated CA-125 levels besides cancer progression. Take-Home Message: CA-125 levels in patients with endometrial cancer may not always reflect cancer disease progression because levels can be influenced by the presence of HF.